A STUDY ONE CONOMIC STATUS OF UNORGANISED WOMEN CONSTRUCTION WORKERS IN TENKASI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The present study was carried out with women construction workers, working in the Unorganized sector. An attempt has been made in the paper to understand the socio-economic condition of women labourers, nature of their work, their working conditions, wage pattern, wage discriminationand other difficulties faced by them at their work place. In order to assess the economic status of women construction worker in Tenkasi district, 56 women construction workers of Tenkasi district were randomly selected with the help of construction engineers. To analyse wage discrimination and factors influencing the wage of women construction workers in Tenkasi district, Findings show that majority of the migrant women were engaged in the construction industry and were only employed in unskilled and low paying jobs as coolies, labourers and helpers. Women were exploited to a greater degree as they were paid less Compared to men for similar nature of work hours spent on work. The conditions of work in the unorganized sector were unsatisfactory and the problems confronted by them were acute. And that their illiteracy, poverty and indebtedness forced them to work forlower wages and under unjust conditions.